Reinventing Black Visibility in Contemporary Art - Isabel Baggett (UNC Test Journal, 2024)
Artists Kerry James Marshall, Kara Walker, and Peter Brathwaite visualize new narratives navigating Black visibility in the twenty-first century. Their work pursues topics such as race and representation, reflecting their continual need for conversation in our contemporary socio-political climate. Marshall’s reinvention of the color black used for pigmentation makes clear the simplification of race and color while inserting Black people into art history using well-known motifs from Western art. Walker appropriates, deconstructs, and recontextualizes antebellum caricatures of Black people through silhouettes that blur the lines between black and white and conflate our past and modern conceptions of race. Marshall and Walker’s artwork provides context for the largely unresearched artist Brathwaite and his Twitter series #RediscoveringBlackPortraiture. After the Getty Museum launched the #GettyMuseumChallenge during the COVID-19 pandemic, performing artist Brathwaite began exploring visual art by placing himself into famous works recreated with photography for social media. All three artists explicitly incorporate themes of identity and reflect on what it means to be Black during a contemporary movement which diverges from framing art around race. By contextualizing Marshall’s, Walker’s, and Brathwaite’s work within past genres, this paper identifies ways these three artists are reacting to historical conventions, as well as contemporary dialogue surrounding race, and fellow artists.